2020
DOI: 10.1002/acm2.12873
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stereotactic body radiotherapy (SBRT) using flattening filter‐free beams on cardiac implantable electronic devices (CIEDs) in clinical situations

Abstract: Purpose: This study focused on determining risks from stereotactic radiotherapy using flattening filter-free (FFF) beams for patients with cardiac implantable electronic device (CIEDs). Two strategies were employed: a) a retrospective analysis of patients with CIEDs who underwent stereotactic radiosurgery (SRS)/SBRT at the Peter MacCallum Cancer Centre between 2014 and 2018 and b) an experimental study on the impact of FFF beams on CIEDs.Methods: A retrospective review was performed. Subsequently, a phantom st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…While a local ICD dose rate of less than 1200 cGy/min may be applied for a short period [4], our data suggest in comparison that with increasing time and radiation dose, much lower dose rates already result in ICD errors. Hurkmans et al have suggested for FFF beams, that at the location of a CIED outside of the target volume, the LDR would be lower than 100 cGy/min and therefore dose-rate effects are rare [16].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While a local ICD dose rate of less than 1200 cGy/min may be applied for a short period [4], our data suggest in comparison that with increasing time and radiation dose, much lower dose rates already result in ICD errors. Hurkmans et al have suggested for FFF beams, that at the location of a CIED outside of the target volume, the LDR would be lower than 100 cGy/min and therefore dose-rate effects are rare [16].…”
Section: Discussionmentioning
confidence: 68%
“…A recent review on 13 lung cancer SBRT cases and a phantom study with explanted ICDs showed that even though no CIED failures were reported on the historical SBRT cohort, in vitro data suggest inappropriate sensing (IS) starting at a dose rate (DR) of 1200 cGy/min (200 mGy/s) when CIEDs were placed within the radiation field. Nevertheless, in the same phantom study, no radiation-induced effects were observed in 6 MV photon beams when a total number of 10 ICDs were placed up to 3 cm away from the PTV in clinical lung cancer SBRT scenarios [ 4 ]. In this study, specific DR effects in ICDs were not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…in which severe failures occurred in the ICP, such as pulse-amplitude changes >25% at cumulative doses of 120 Gy and the loss of telemetry capability at cumulative doses of 130 Gy [ 13 ]. However, in a similar study with 10 MV-FFF, CIEDs included in a portion of the irradiated field were observed to have pacing rate reprogramming, pacing threshold reprogramming, and pulse width reduction, at a cumulative dose of 26, 42.7 and 46.4 Gy, respectively [ 20 ]. It was different from ICP failure and the cumulative dose at which ICP failure was induced, compared to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Aslian et al. performed a partial direct irradiation of CIED with FFF beams using VMAT [ 20 ]. No abnormality was observed with 6 MV-FFF in all CIEDs, whereas reprogramming and reduction of pacing pulse width were observed with 10 MV-FFF at cumulative doses of <50 Gy in less than half the CIEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that higher energy radiation (ie, >10 MV) will cause more IDs to experience electric malfunction 14 , 15 , 16 , 17 , 18 , 19 , 31 , 32 , 33 , 34 , 35 , 37 , 38 , 39 ; as a result, devices with electronic circuits should be treated with low energy (ie, <10 MV photons) only. 40 Because both severity and risk of failure of devices from dose rate effects are mild and low, 41 the AAPM TG-203 recommends a dose rate of <0.2 Gy/min as guidance. A recent study investigated the effects of x-ray dose rates of 4 to 24 Gy/min on CIED function and found that a dose rate >8 Gy/min would cause a temporary malfunction due to interference.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%